The Impact of Migration on Food Consumption Patterns : The Case of Vietnam - Nguyen, Minh Cong; Winters, Paul (2012)
This paper explores the relationship between migration and consumption patterns using panel data from the 2004 and 2006 Vietnam Household Living Standards Surveys. Employing an instrumental variable approach to control for the endogeneity of migration, our results indicate that short-term migration has a positive effect on overall per capita food expenditures, per capita calorie consumption and food diversity. Long-term migration also appears to be positively related to consumption, but impacts are often insignificant and of a lesser magnitude than short-term migration. The results provide no evidence of negative effects of migration, and support the view that short-term migration is a mechanism by which households maintain food security. The results suggest that to improve food security the Vietnamese government should enact policies that facilitate short-term migration flows as well as the transferring of remittances.